Optimization of Character Education through Strengthening the Values of the Bugis Society (Macca and Lempu) - Hamsah Hamsah; Romi Mesra; Sopian Tamrin (JED (Jurnal Etika Demokrasi), 2024)
The educational compass deliberately directs students to meet the demands of the world of work. Local content as the basis for character learning is increasingly marginalized and almost difficult to find in schools. In fact, the character aspect is very determining in preparing competitive educational outcomes, including the demands of the world of work. Based on this concern, this article aims to reaffirm the importance of character education in the world of education, especially learning the value of  macca and lempu (Smart and Honest) in the Bugis community. This article is classified as a qualitative type with a library study method. Based on literature searches, it is confirmed that character education through learning local wisdom, the values of macca and lempu in Bugis society, is very important. Schools as educational institutions are socialization agents that are most likely to teach local wisdom systematically and structured to children amidst the penetration of foreign culture. Therefore, the educational curriculum through local wisdom lessons not only needs to be maintained, but also needs to be strengthened by placing it as the fulcrum for building the future character of the nation's children. Character strengthening strategies can be carried out through learning, appreciation, strengthening and habituation. The values of macca (intelligent) and lempu (honest) work together to form a character who is not only intellectually intelligent but also has integrity and honesty. In conclusion, character education is an inseparable part of preparing students to face global challenges, including the needs of the world of work.